Using Carbon Nanotube Filtration Technology and Ceramic Filter ‎Membranes to Remove Salts from Oil Effluents ‎ (Journal of University of Babylon for Engineering Sciences, 2025)
The performance of two types of reverse osmosis membranes, namely the Carbon Nano-Tube Filtration Membrane and the Ceramic Filtration Membrane, was evaluated in this study by comparing the removal efficiency of the conventional plant in the refinery and the reverse osmosis removal efficiency, after tracing the treated wastewater streamline in the Al-Qayyarah refinery treatment plant. In both membranes, the treated water has pH is 6.4, 6.2, lead (Pb) is 0.0449, 0.0016, cadmium (Cd) is 0.00443, 0.00255, copper (Cu) is 0.00443, 0.00255, cobalt (Co) is 0.0031,  0.00041, Total E-coli is 39, 27, conductivity less than 97, 83 μS/cm, (SO4) less than 9.15, 4.416 ppm, chemical oxygen demand  less than 9.346, 7.861 ppm, calcium carbonate (CaCO3) less than (4.3, 1.1 mg/L), Sodium (Na+) is 2.1, 2.61ppm, and total nitrogen (TNO3 or NO3) less than 0.34, 0.06 ppm, Orthophosphate (PO4) is 0.081, 0.002, Sulfate (SO4) is 9.15, 4.416 , for Carbon Nano-Tube Filtration Membrane and the Ceramic Filtration Membrane, respectively. It concluded that the Carbon Nano-Tube Filtration Membrane  is more efficient in terms of treatment, and the Ceramic Filtration Membrane has a stronger texture and longer working life. The proposed treatment strategy is expected to make a significant reduction in the amount of water in refinery primary water withdrawal possible as a result of its reuse in the cooling system.